Vildagliptine protects SH-SY5Y human neuron-like cells from Aβ 1–42 induced toxicity, in vitro - Dokumacı, Alim Hüseyin (Cytotechnology, 2019)
The amyloid β (Aβ) toxic fibrils is thought to play a central role in the onset and progression of Alzheimer’s disease (AD) because of it is a main formation of senile plaques. Diabetic patients are more vulnerable to caught Alzheimer’s disease. Vildagliptine, a novel anti diabetic agent, has been reported to exert protective effects on AD rat models in restricted study. We aimed to investigate any protective effects of vildagliptine against Aβ fibrils on SH-SY5Y cell line. Vildagliptine decreased PSEN1 and PSEN2 mRNA levels which enroll Aβ production. In addition, vildagliptin was downregulated caspase-3 and caspase-9 expression levels which were evoked by Aβ. Also we confirmed cellular viability with real time cell analyzer and MTT assay. Our data exposed that vildagliptine has lowering effect on GSK3β and Tau phosphorylation. However we did not get protective effect of vildagliptine against Aβ toxicity on mitochondrial membrane potential. These results indicate that vildagliptine exerts a protective effect against Aβ by decreasing apoptosis related proteins, lowering GSK3β and Tau phosphorylation levels in addition to expression of PSEN1 and PSEN2 mRNA downregulation effect.